The controversial Brazilian welfare regime - Lena Lavinas; Denise Gentil; Barbara Cobo (United Nations Research Institute for Social Development (UNRISD), 2017)
The turn of the century brought encouragement and hope for many emerging economies undergoing a new phase of growth, with falling inequality and a promising push towards greater social inclusion. Within this trend of economic recovery and increased equity, Latin America would stand out, with Brazil taking a place of pride. Both the country and the region saw a significant drop in their notoriously high levels of income inequality and poverty over the course of the first decade of the century. Brazil ultimately became a conduit for broader hopes of overcoming underdevelopment, standing as a benchmark for a new model of inclusive growth, both in Latin America and across the countries of the Global South. Indeed, from 2003 to 2013, the Gini index for per capita household income slid from 0.594 to 0.525 (IBGE- PNAD 2003-2013), while the share of poor population shrank noticeably: in 2013 the poor stood at 14.6 million, 7.6 percent of the population, as opposed to 47 million or 27.7 percent ten years earlier This paper aims to address the role played by social policies and the social protection system in paving a new economic regime in Brazil (social developmentalism), and examine the kind of coordination between macroeconomic policies and social spending that ultimately prevailed in both cycles (growth and recession). This will mean analysing the link between the expansion of the economy and the existing social protection system to grasp new social policy arrangements that emerged as of late. [...] In driving on commodification, this model weakened the ongoing consolidation of the social security system, reinforcing dynamics that segment, discriminate and condition access to social rights. The welfare regime that is surfacing is nothing more than an additional function now attributed to social policy - in this case, custom-fit to the logic of financial capitalism.
Additional information: Prepared for the UNRISD project New Directions in Social Policy: Alternatives from and for the Global South
Keywords: 330; Brazil; social protection; financialization; welfare regimes; social security; recommodification